AB0668 Joint hypermobility, growing pains and obesity are mutually exclusive as causes of musculoskeletal pain in schoolchildren. (23rd January 2014) - Sperotto, F.; Balzarin, M.; Parolin, M.; Monteforte, N.; Vittadello, F.; Zulian, F.
Abstract : Background: Chronic Musculoskeletal pain (MSP) is common in children and can be due to several non-inflammatory conditions such as the Benign Joint Hypermobility Syndrome (BJHS) and Growing Pains (GP). Since these conditions are often misdiagnosed, affected children frequently undergo several and sometimes invasive procedures which may delay the diagnosis. Objectives: Aim of the study was to evaluate prevalence and clinical features of chronic non-inflammatory MSP in schoolchildren and to analyze causes and possible risk factors associated with this condition. Methods: We conducted a cross sectional study in a cohort of healthy schoolchildren, aged 8-13 years, by collecting information and performing a physical examination. The clinical history was focused on presence and sites of MSP, defined as continuous or recurrent pain lasting more than 3 months, during the previous 6 months, with an intensity so high to interfere with the regular activities of daily living. We also investigated type of sport activities, presence of GP, defined as cramping bilateral limb pain typically occurring in the evening or at night and associated with a normal physical examination and family history for MSP. Clinical examination included body mass index, pubertal stage and musculoskeletal exam focused on the presence of hypermobility according with the Beighton Criteria (Beighton score ≥4/9). Results: 289 schoolchildren, 143 females and 146 males, entered the study. Chronic MSP occurred in 30.4% of subjects, BJHS occurred in 13.1%. GJH was more frequent in symptomatic subjects than in asymptomatic ones (p= 0.054). Symptomatic subjects were more frequently pre-pubertal than pubertal (p=0.006). In general, GP, BJHS and obesity (OB) were mutually exclusive as causes of MSP as, among 88 symptomatic subjects, 52.3% had GP, 40.9% presented BJHS, 4.5% were OB and only two (2.3%) presented both BJHS and OB. After puberty, GP persisted in 66.7%, BJHS in 26.7% and in association with OB in 6.7%. Conclusions: Approximately one third of schoolchildren suffer from MSP. These subjects should be carefully evaluated for the presence of GP, GJH and OB, which are mutually exclusive as causes of MSP. Pubertal stage plays an important role in the physiopathology of this condition and further studies are needed to explore this relationship during time. References: Kirk JA, Ansell BM, Bywaters GL. The hypermobility syndrome: musckuloskeletal complaits associated with generalized joint hypermobility. Ann Rheum Dis 1967;26:419-425. Beighton P, Soloman L, Soskolne CL. Articular mobility in an African population. Ann Rheum Dis 1973;32:413-8. Peterson H Growing pains. Pediatr Clin North Am. 1986; 33: 1365-72. Disclosure of Interest: None Declared